Spicing Up Meat Preservation: Cinnamomum zeylanicum Essential Oil in Meat-Based Functional Foods—A Five-Year Review - Raluca-Aniela Gheorghe-Irimia; Dana Tăpăloagă; Paul-Rodian Tăpăloagă; Oana-Mărgărita Ghimpețeanu; Laurențiu Tudor; Manuella Militaru (Foods, 2024)
Today, in the modern consumer era, we are facing a significant change in terms of preferences and behaviour. This tendency is not only a basic desire, but rather a significant social and cultural movement that exerts a tremendous influence on the food industry and correlated sectors. In this direction, food authorities and experts have thoroughly evaluated the practicality of employing natural preservation methods to enhance the quality and safety of foodstuffs, while preserving their nutritional and sensory attributes. Given this context, the development of meat products enhanced with Cinnamomum zeylanicum essential oil (CZEO) poses promising avenues, such as extended shelf-life due to its antimicrobial, antifungal, and antioxidant properties. CZEO also has many health benefits, rendering it as a promising ingredient in functional meat product formulations. Conversely, challenges such as higher associated costs, sensory interactions, and variability arise. Hence, the aim of this review is to offer a novel critical perspective on CZEO’s potential application as a functional ingredient in meat products formulations and to address the inherent associated challenges, based on the last five years of scholarly publications.